Strange Storms: Rainfall Extremes From the Remnants of Hurricane Ida (2021) in the Northeastern US. Issue 3 (16th March 2023) - Smith, James A.; Baeck, Mary Lynn; Su, Yibing; Liu, Maofeng; Vecchi, Gabriel A.
Abstract: On 1 September 2021, the remnants of Hurricane Ida transformed into a lethal variant of tropical cyclone in which unprecedented short‐duration rainfall from clusters of supercells produced catastrophic flooding in watersheds of the Northeastern US. Short‐duration rainfall extremes from Ida are examined through analyses of polarimetric radar fields and rain gauge observations. Rainfall estimates are constructed from a polarimetric rainfall algorithm that is grounded in specific differential phase shift ( K DP ) fields. Rainfall accumulations at multiple locations exceed 1000‐year values for 1–3 hr time scales. Radar observations show that supercells are the principal agents of rainfall extremes. Record flood peaks occurred throughout the eastern Pennsylvania—New Jersey region; the peak discharge of the Elizabeth River is one of the most extreme in the eastern US, based on the ratio of the peak discharge to the sample 10‐year flood at the gaging station. As with other tropical cyclones that have produced record flooding in the Northeastern US, Extratropical Transition was a key element of extreme rainfall and flooding from Ida. Tropical and extratropical elements of the storm system contributed to extremes of atmospheric water balance variables and Convective Available Potential Energy, providing the environment for extreme short‐duration rainfall from supercells. Key Points: Remnants of Hurricane Ida produced unprecedented short‐duration rainfall extremes at 1–3 hr time scale Supercells were the principal agents of extreme rainfall and flooding Extratropical Transition of Ida contributed to the environment of record short‐duration rainfall